Central nuclear counts in muscle fibres before and during treatment in hypothyroid myopathy. Issue 3 (March 1979) - McKeran, R. O.; Ward, P.; Slavin, G.; Paul, E. A.
Abstract : Serial percutaneous needle muscle biopsies of vastus lateralis were studied in 10 patients who had varying degrees of hypothyroid myopathy. The biopsies were taken before and during treatment with l -thyroxine. Before treatment the most severely clinically affected patients showed type II muscle fibre atrophy and loss, together with increased central nuclear counts preferentially affecting the type II muscle fibre. Both the type II muscle fibre atrophy and loss and the increased central nuclear counts tended to return towards normal values during treatment with l -thyroxine. The severity of myopathic symptoms before and during treatment correlated with the biochemical evidence of hypothyroidism, a type II fibre atrophy, and increased central nuclear counts. The severity of myopathic signs before and during treatment was correlated with both a type II fibre atrophy and loss and increased central nuclear counts. There was no evidence that the myopathic signs before and during treatment were related to the biochemical parameters of hypothyroidism, except the level of thyroid stimulating hormone. It is suggested that sequential studies of muscle fibre percentages, diameters, and central nuclear counts may provide an additional method of assessing the response to treatment in hypothyroid and possibly other types of myopathy. When increased central nuclear counts are confined to a specific muscle fibre type, this may suggest a hitherto unsuspected specificity of muscle fibre damage.